Comparative study on the tribological properties of laser post-treated and untreated AISI304 stainless steel matrix composite reinforced with hard ceramic particles (TiB2–TiN–SiC) and prepared by ex-situ P/M route. Issue 15 (15th October 2019) - Misra, Debjit; Barange, Sumit; Joardar, Hillol; Kumar, Jitendra; Das, Alok Kumar; Mukhopadhyay, Suman; Chatterjee, Satyajit
Abstract: This work highlights evaluation of suitable process parameters to result significantly higher hardness, fracture toughness and wear resistance in metal matrix composites (MMC) developed with different proportions of reinforcements, namely, TiB2, TiN, and SiC in steel (AISI 304). The composites are developed through powder metallurgical route and are subsequently laser surface glazed. Thorough characterizations of composites' mechanical and tribological behaviors before and after laser surface treatment and application of response surface methodology (RSM) for modeling and analysis of its behavioral responses towards variations in process parameters are performed.